Peritendinous Submembrane Access Technique for Management of Acute Ruptures of the Achilles Tendon: A Retrospective Study of 249 Cases - Xin Huang; Jia‐Wei Liu; Yu Jiang; Hong‐Wei Zhu; Xing‐Xing Hu; Ke‐Jian Wu; Xiao‐Ning Wang; Shuai Zhang (Orthopaedic Surgery, 2024)
Objective Percutaneous repair is an alternative to open surgical repair of the Achilles tendon with comparable, functional results and low re‐rupture and infection rates; however, sural nerve injury is a known complication. The purpose of this study is to design a new surgical procedure, the minimally invasive peritendinous submembrane access technique (MIS‐PSAT). It offers optimal results, with excellent functional outcomes, and with minimal soft tissue complications and sural nerve injury. Methods This retrospective study included 249 patients with acute closed Achilles tendon ruptures treated at our institution between 2009 and 2019. All patients underwent MIS‐PSAT at our institution and were followed up for 8–48 months. Functional evaluation was based on the Achilles tendon total rupture score (ATRS) and the American Orthopedic Foot and Ankle Society Ankle‐Hindfoot Scale (AOFAS‐AHS), associated with local complications and isokinetic tests. Results None of the patients had infection, necrosis, or sural nerve injury. Re‐rupture occurred in two cases. The average times to return to work and sports was 10.4 and 31.6 weeks, respectively. The average ATRS and AOFAS‐AHS scores were 90.2 and 95.7, respectively, with an excellent rate of 99.5%. Isokinetic tests showed that ankle function on the affected side was comparable with that on the healthy side (p > 0.05). Conclusion The MIS‐PSAT for acute Achilles tendon rupture is easy to perform with few complications. Importantly, the surgical technique reduces the risk of sural nerve injuries. Patients have high postoperative satisfaction, low re‐rupture rates, and muscle strength, and endurance can be restored to levels similar to those on the healthy side.